Self-Injury and the Use of Behavioral Interventions: A Synthesis of Single Case Studies. Issue 2 (1st June 2016) - Robinson, Audrey; Quast, Heather; Davis, Jordan; Riley, Shanda; Hott, Brittany; Simpson, Chris
Abstract : Behavioral interventions are prevalent in addressing non-suicidal self-injury (NSSI). This manuscript examines the effects of behavioral interventions on diminishing self-injurious behaviors. Eight single-case experimental designs published between 1999 and 2013 were reviewed and evaluated for participants, data collection procedures, self-injurious behaviors, diagnosis, and treatment setting. The interventions were then examined for effectiveness by calculating Percent of Non-overlapping Data (PND) and Percentage of Data Exceeding the Mean (PEM). Results indicate significant decreases in NSSI for interventions such as combinations of differential reinforcement (DRO), extinction, blocking, and positive behavior support (PBS). Implications for practice and future research directions are reported.